Anterior cruciate ligament insufficiency: a dynamic three-dimensional motion analysis - Marans, H J; Jackson, R W; Glossop, N D; Young, C (The American journal of sports medicine, 1989)
An electrogoniometer, capable of measuring all six degrees of freedom of knee movement, was developed in our laboratory. This Instrumented Spatial Linkage system was then used to generate data for a three-dimensional assessment of 20 ACL deficient and 30 normal subjects during level walking. The system proved to be a viable method for describing total knee motion. We found the ACL deficient knees to have increased anterior/posterior translation and significant pattern differences compared to the controls. The results of this study may have implications in the treatment of the ACL deficient patient.